VEGETATION ANALYSIS AND CARBON STOCK ESTIMATION IN KUNINGAN BOTANICAL GARDEN WEST JAVA - Astari, Wiwit
Kuningan Botanical Garden (KBG) which was inaugurated in 2015, is the youngest botanical garden in Indonesia. This botanical garden was built with the aim of conservation, education, research, ecotourism and provision of environtmental services such as carbon stock, protection of water systems and disaster control. Research on insects and plant pests has been carried out in the Kuningan Botanical Garden but there is still little information about plant species diversity and carbon stock estimation. This research was conducted to record the diversity of plant species and calculate the estimation of carbon deposits in the Kebun Raya Kuningan West Java. Data collection was carried out on 20 nested plots measuring 20m × 20m which were determined by systematic with random start and purposive sampling to obtain standing tree data. The 10m × 10m subplots are placed within a 20m × 20m plot to obtain pole data; 5m × 5m subplots for bushes and stakes data; and 2m × 2m subplots for seedlings and herbaceous data. The parameters calculated for trees, poles and stakes are DBH (Diameter at Breast Height), height, number of individuals, basal area, density, and frequency, while for seedlings, shrubs, and herbs the parameters calculated are the number of individuals, frequency, and exuberance. Collecting understorey, litter and soil biomass data was carried out utilizing destructive method in 1m × 1m subplots within a 20m × 20m plot. Important Value Index (IVI) and diversity index were calculated using vegetation analysis data. Tree biomass is calculated using allometric equations (Haruni et al., 2012), while understorey biomass, litter, and soil are calculated based on SNI No. 7724 and SNI No. 7725 (2011). The results showed that the Schima wallichii (IVI: 46.22%) and Gmelina arborea (IVI: 30.24%) were the dominant tree species found in KRK. Plants with pole levels are dominated by the Schima wallichii (IVI: 65.87%) and Gnetum gnemon (IVI: 39.11%). Adenanthera Pavonina and Gnetum gnemon with IVI 41.56% are the dominant seedlings. Plants with shrub life forms are dominated by Mimosa invisa (IVI: 59.42%) and Mimosa pudica (INP: 42.90%); and herbs are dominated by Centrocema pubescens (IVI: 26.52%) and Paspalum cartilagineum (IVI: 25.91%). The tree diversity index in this botanical garden is 2.8. The estimation of carbon deposits in tree stands is 25.45 tonC / ha (11.06%), in understorey is 11.29 tonC / ha (4.9%), in litter is 6.32 tonC / ha (2.75 %), on necromass is 0.17 tonC / ha (0.07%), and soil organic carbon is 186.85 tonC / ha (81.21%). The total estimated carbon stock in Kuningan Botanical Garden West Java within an area of 156.4 ha are 35985 tons.